The Role Of The Family In Character Education In The Workforce Family : The Case Study In The Village Ngumpul, Balong, Ponorogo - Moh Alwi Yusron; Muhammad Dimas Bagus Nurmuzayyin (Educan : Jurnal Pendidikan Islam, 2018)
The loss of one individual in the family can be a cause of the formation of a child's character is less than optimal and this incident is often the case in the family of Indonesian workers. But not all children who grow up in the family of Indonesian workers have a bad character, because there are still families who can form their children to grow with good character even though they have to lose one parent to work. The purpose of the study is: (1) To find out the role of the family in forming character in the families of migrant workers in the Ngumpul Village, Balong District, Ponorogo Regency, (2) To find out the supporting factors and inhibiting factors of character formation in the families of migrant workers in the Ngumpul Village, Balong District, Ponorogo Regency.From the results of the research researchers found that there are family roles in shaping the character of families of migrant workers.these roles are : 1) Embedding religious values, 2) getting used to doing good, 3) being an example and replacing the position of the mother, 4) giving assignments, 5) instilling the nature of independence, 6) inviting discussion. The attitudes held by educators in thefamilies of migrant workers in character building efforts are: 1) patient, 2) sincere, 3) firm, 4) openness between family members.Supporting factors in character building in the families of migrant workers are: 1) home environment, 2) school environment, 3) work environment, 4) community environment.